Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1053/j.ajkd.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcome Instruments for Physical Symptoms Among Patients Receiving Maintenance Dialysis: A Systematic Review

Abstract: Background Patients with end-stage renal disease (ESRD) receiving dialysis have poor health-related quality of life (HRQoL). Physical symptoms are highly prevalent among dialysis-dependent patients and play important roles in HRQoL. A range of symptom assessment tools have been used in dialysis-dependent patients, but there has been no previous systematic assessment of the existing symptom measures’ content, validity, and reliability. Study Design systematic review of the literature Settings & Population E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 90 publications
0
57
0
3
Order By: Relevance
“…[15] The review yielded 23 PROMs containing 3 or more physical symptoms. Thirteen of the 23 PROMs were developed in patients receiving dialysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] The review yielded 23 PROMs containing 3 or more physical symptoms. Thirteen of the 23 PROMs were developed in patients receiving dialysis.…”
Section: Resultsmentioning
confidence: 99%
“…We followed a 4-step process in developing the hemodialysis symptom PROM: (1) literature review (previously reported[15]); (2) concept elicitation interviews; (3) item selection and draft measure construction; and (4) 3 rounds of cognitive debriefing interviews with intervening measure updates (Figure 1). Advisors, including nephrologists, psychometricians, and patients, provided input during the measure development process.…”
Section: Methodsmentioning
confidence: 99%
“…The Palliative Outcome Score‐Renal (POS‐Renal) questionnaire, validated for use in patients with advanced kidney disease and recommended by recent guidelines, was used to survey symptoms . The POS‐Renal lists the same 17 symptoms (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…(17) Within other branches of oncology, ESAS has been used by medical oncologists,(59, 60) radiation oncologists,(61) surgical oncologists,(62, 63) and gynecological oncologists. (64, 65) Outside of oncology, ESAS has also been adopted for symptom assessment in patients with kidney diseases,(66, 67) heart failure,(68, 69) pulmonary disorders,(70) hepatic diseases,(71) and sickle cell anemia. (72)…”
Section: Present Applicationsmentioning
confidence: 99%